A Laryngopharyngeal Mass: Pressure Effect of the Superior Cornu of the Thyroid Cartilage Induced by a Thyroid Mass - Siti Farhana Abdul Razak; Mawaddah Azman; Loong Siow Ping (Oman Medical Journal)
The superior cornu of the thyroid cartilage is a versatile structure, and anatomical variations can lead to diverse clinical presentations. We describe a case of a patient with a medialized superior part of the thyroid cartilage caused by pressure from a large thyroid mass, detected during laryngoscopy before thyroidectomy. A neck computed tomography scan revealed an elongated and medially displaced superior cornu of the right thyroid cartilage, resulting from the push exerted by the right thyroid mass. As the patient remained asymptomatic and refused surgical intervention, no further consideration was given to surgically addressing the medialized superior thyroid cornu.